Publisher Correction: Tuned thalamic excitation is amplified by visual cortical circuits. (September 2018) - Lien, Anthony; Scanziani, Massimo
In the published version of this article, a data point is missing from Fig. 4f, and they -axis label reads "RFpre "; it should read "RFpref ." The original article has not been corrected. The original and corrected figures are shown in the accompanying Publisher Correction.